Maqāṣid Sharīah Paradigm in Wealth Preservation and Regional Stability Through Local Currency Protection within ASEAN - Fikri, Ikhwan; Subroto, Muhammad Al Kautsar (Mazahibuna: Jurnal Perbandingan Mazhab, 2024)
This study explores Indonesia's motivation for promoting Local Currency Settlement (LCS) among ASEAN countries and assesses the outcomes of the 42nd ASEAN Summit through the lens of maqāṣid sharīah, focusing on hifẓ al-māl (wealth preservation). Utilizing a mixed-methods approach, the research combines a literature review with field research. The literature review integrates diverse sources such as journals, books, and online materials relevant to policy analysis, while field research includes interviews with Islamic economists, academics, and leaders from religious and government sectors to understand LCS implementation and impacts. The findings indicate that LCS agreements bolster economic independence and stability in the ASEAN region by enabling transactions in local currencies. This system facilitates bilateral and regional trade, enhances investment flows, and supports various economic activities among ASEAN nations. It aligns with the maqāṣid sharīah principle of hifẓ al-māl and reinforces the qiyām or qawām system (balance within self, family, and society), promoting broader economic stability. This research provides a novel perspective by analyzing LCS within the framework of maqāṣid sharīah, highlighting how regional economic policies can harmonize with Islamic principles of wealth preservation. The results suggest that LCS could be a strategic tool for strengthening regional economic integration and stability. By reducing reliance on third-party currencies and aligning with maqāṣid sharīah principles, LCS has the potential to foster more resilient and balanced economic relationships both within ASEAN and globally.